Fragmentos de um escritor: Ruffato em perspectiva(s) - Silva, Franciele Queiroz da (2012)
The present dissertation investigates the discourses which surround the figure of the contemporary writer Luiz Ruffato. The objective of this work was to analyze some of the author s propositions which appear in interviews, statements and criticisms concerning his production and to oppose them to the analysis of the novel Inferno Provisório. For that, we made a broad investigation of interviews, which, in a first moment, characterized and presented the authorial figure of Luiz Ruffato and which were also our basis to achieve two other aspects of this study: the assumed condition of realistic writer and the discussion related to the form of the novel. The author s presentation in the media, through interviews, enables us to identify the discursive intention of consolidating himself as a professional writer. The perspective of media and professional writer discussed here shows us another facet of an authorial figure which marks the contemporary scenario: Luiz Ruffato as a carrier of realistic heritages. The notion of realistic writer, which also surrounds his discourses, points out the necessity to forge tools to detect the narrative and performative strategies of language, refusing the assumption of a traditional realism concerning the contemporary production. The necessity of discussion regarding the ―novel‖ form comes with the premise of novel-installation. Considering the installation as one more facet of the hybrid characteristic which marks the novel as form, Luiz Ruffato seems to experiment and radically conceive form to overcome the mere notion of representation as portrait of reality.